Cultural context and mental health: a Kenyan elite athlete's perspective - Kirkland, A.; Whittaker, A. C.; Boit, M.; Chinn, S.; Crawley, M.; Ndetei, D.; Ochieng, P.; Stirling, E.; Chesire, I. (Sports Medicine, 2025)
The causes of mental ill health in elite athletes are complex, influenced by socioeconomic and cultural factors. These factors are important in shaping discussions surrounding the mental health of athletes and the design of subsequent interventions to support them. However, such consideration is rare, particularly when considering the mental health of athletes in low- and middle-income countries. Therefore, this Current Opinion draws on behavioural change science and multi-disciplinary expertise in elite sport, medicine, health, psychology, coaching and anthropology in the context of elite runners in Kenya. The material conditions in this country are reflected in the prevalence of poor mental health and treatment availability. We explore the mental health of elite Kenyan runners within this context and provide recommendations surrounding the treatment of mental health conditions in elite sport globally. We conclude that a consensus on the mental health of elite athletes must be informed by contextual factors, including affordability, appropriateness, availability, and accessibility of mental health services relating to local conditions. This context-specific approach could be expanded to mental health in settings other than sport such as youth organisations.